2015
DOI: 10.1007/s11764-015-0447-x
|View full text |Cite
|
Sign up to set email alerts
|

Active transportation in adult survivors of childhood cancer and neighborhood controls

Abstract: Purpose Childhood cancer survivors (CCS) are at high risk of treatment-related late effects, including cardiovascular disease and diabetes, which can be exacerbated by inadequate physical activity (PA). Previous PA interventions targeting CCS have focused on the domain of leisure-time/recreational PA. Active transportation, another domain of PA, has not been described in CCS. Therefore, this study aimed to identify active transportation behaviors, barriers, and correlates in adult CCS. Methods We recruited 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…The most common measure was marital status. Most (n = 17) studies reported that marital status and length of marriage were unrelated to PA. Three studies documented positive associations between being married or partnered and PA, two reported significant associations that became nonsignificant in multivariate models, and three reported associations with some types of, but not total, PA . Number of children and being a member of a community organization were not associated with PA.…”
Section: Resultsmentioning
confidence: 94%
“…The most common measure was marital status. Most (n = 17) studies reported that marital status and length of marriage were unrelated to PA. Three studies documented positive associations between being married or partnered and PA, two reported significant associations that became nonsignificant in multivariate models, and three reported associations with some types of, but not total, PA . Number of children and being a member of a community organization were not associated with PA.…”
Section: Resultsmentioning
confidence: 94%
“…Future work should draw upon previous findings that have shown efficacy in this population, including the use of biochemical verification in tobacco interventions; assisting with decision making related to substance use; and using Web sites, videogames, and other electronic formats to encourage healthy eating. Designing physical activity interventions that use group exercise or increase self‐efficacy as well as promoting ecologic/environmental interventions, such as active transportation and adventure‐based training, are areas to explore. Interventions that target alcohol use, sunscreen behavior, and risky sexual behavior are limited and require further investigation.…”
Section: Health Behaviorsmentioning
confidence: 99%
“…Across the scoped articles, survival disparities, primary care, and body size and weight management were the main themes. Neighborhood factors to study these themes were: nSES, exercise opportunities [ 73 , 74 ], access to healthy food options [ 73 ], and access to health care facilities [ 44 ]. One study found that obese survivors of pediatrics cancers were more likely to live in neighborhoods with lower SES [ 73 ].…”
Section: Resultsmentioning
confidence: 99%